P417 Seroconversion after COVID-19 Vaccination in Inflammatory Bowel Disease Patients. (21st January 2022) - Horvath, M; Csontos, Á A; Sárközi, M; Cseprekal, O; Szijártó, A; Miheller, P
Abstract: Background: Data about the effect of different immunosuppressive treatments of IBD patients on seroconversion and on different SARS-CoV-2 vaccinations are scarce. To avoid impaired vaccine responses and worse outcome of COVID-19, factors attenuating protective immunity shoud be shought. Methods: Anti SARS-CoV-2S antibody levels of IBD patients in remission were measured by immunoassay (Roche) before vaccination and on the second week. Antibody responses were compared among different treatment groups (biologics, combination, azathioprin, without immunomodulation) and between mRNA and other type of vaccines. Anti TNF alpha levels were also assesed, 24 hours before vaccination considering correlation with seroconversion. Results: Thirty-eight (31.7%) ulcerative colitis and eighty-two (68, 2%) Crohn's disease patients were included (median age, 39.1 years, 53.3% female). No serious comorbidities were present. Eighty-two patients (68.3%) were on biological therapy, fifty-two (43%) were treated with azathioprine alone or in combination. Two doses of mRNA vaccines were administered to ninty-eight patients ((81, 7%) Moderna:, 20, Pfizer:, 78). The other type of vaccines were AstraZeneca (16) Sputnik V (3) and Sinopharm (3). The median anti-SARS-CoV-2S antibody level was, 2733 U/mL (IQR:, 535–7764) on the, 14th day after vaccination (IQR:, 14–17). Significant differences were revealed between the groups of patients treated with biological agents or non-biological therapy (median:, 1649 U/ml vs., 5711.5 U/ml; p=0.013) and between patients recieving mRNA and non-mRNA vaccine (median:, 3367.5 U/ml vs., 392.6 U/ml;p<0.001). Considering the varying effect of immunosupression related to combination therapy, biological drugs, azathioprin and other non-immunomodulating treatments antibody response were assesed in these groups also. The median antibody levels were, 850, 5 U/ml (IQR:, 251.0–4899.5), 1837 U/ml (IQR:, 544.5–5902), 3141 U/ml (IQR:, 1066–7988), 7764 U/ml (IQR:, 5601–13808) demonstrating significant differences among them (p<0.001). No correlation between anti-TNF-alpha serum level and antibody response were found. Conclusion: Altough all vaccines cause seroconversion in IBD patients who are in remission, the rate of seroconversion is lower in patients treated with immunosupressant, biological agent or combo therapy or recieving non-mRNA vaccines. As the level of anti-TNF-alpha agents do not affect the rate of seroconversion there is probably no need for matching the time of vaccination and anti-TNF therapy.